Case Report: Necrotizing pneumonia in pediatric patients: a rare case of unilateral necrosis in two entire lobe tissues - Zhang, Jingli; Zhang, Yingqian; Gao, Longfei; Wu, Huifang; Liu, Xiaojuan; Yang, Fan; Wang, Yingxue (Frontiers in Pediatrics, 2025)
Background Necrotizing pneumonia is a serious complication of Mycoplasma pneumoniae infection, especially in pediatric patients. Although necrotizing pneumonia is a rare condition, the occurrence of unilateral necrosis in two entire lobe tissues is even rarer. This case study presents a 5-year-old male child with necrotizing pneumonia caused by Mycoplasma pneumoniae, describing the clinical features, laboratory abnormalities, and radiographic findings associated with this condition, particularly the rare occurrence of unilateral necrosis in two entire lobe tissues. Case presentation The patient presented with a 14-day history of fever and cough, accompanied by paroxysmal cough with continuous sounds, congested throat, increased respiratory effort, and abnormal lung findings on physical examination. Laboratory investigations revealed elevated white blood cell count, increased inflammatory markers, elevated liver enzymes, coagulation dysfunction, and hypoalbuminemia. Imaging studies showed the presence of pleural effusion and progressive necrotizing pneumonia, including the rare occurrence of unilateral necrosis affecting both entire lobe tissues. Conclusion Necrotizing pneumonia caused by Mycoplasma pneumoniae infection can present with prolonged fever, elevated inflammatory markers, pleural effusion, and progressive necrosis of lung tissue, with the occurrence of necrosis observed unilaterally in both entire lobe tissues is even rarer. Monitoring D-dimer levels is essential for evaluating the possibility of necrotizing pneumonia. Early recognition and appropriate management are crucial to improve outcomes in these patients.